Field notes contributed by Ramona R. Sommerlot, fall 1986 - Sommerlot, Ramona R.et al (1986)
List of birds and locations contributed by Ramona R. Sommerlot. Field notes include sighting of an Albino Barred Owl in Hardin County. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed/flatbed